Perencanaan Strategis Sistem Informasi dengan Model Be Vissta Planning (BVP) Pada UMKM Obat Luar - Sutrisno, Ezra Harfi; Fibriani, Charitas (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Moonlight Store is a business engaged in the sale of herbal medicines. Currently, the competition between MSMEs is considered very high so that it can threaten the Moonlight store's business process. The Moonlight store needs to take advantage of the development of information technology and develop a strategy that is in accordance with the vision and mission of the Moonlight store. The process of formulating an information system strategy in this study uses the be-vissta planning model. This model applies technical analysis so that it can then develop a strategic information system plan that can be applied to Moonlight stores to face business competition.